2007
DOI: 10.1038/oby.2007.190
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight Correlates Differently with Cardiovascular Risk Factors in Youth

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 33 publications
4
39
0
3
Order By: Relevance
“…Our data demonstrated that high BW girls had two times higher odds of being OW/OB, while boys had 1.65 times higher odds of being classified as OW/OB, which is consistent with other studies showing a positive association between BW and further prevalence of obesity in both children a adolescents (Curhan et al, 1996, Dubois and Girard, 2006, Wei et al, 2007.…”
Section: Insert Figure 1 Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data demonstrated that high BW girls had two times higher odds of being OW/OB, while boys had 1.65 times higher odds of being classified as OW/OB, which is consistent with other studies showing a positive association between BW and further prevalence of obesity in both children a adolescents (Curhan et al, 1996, Dubois and Girard, 2006, Wei et al, 2007.…”
Section: Insert Figure 1 Discussionsupporting
confidence: 82%
“…Several studies have addressed the association between BW and late development of cardiovascular diseases (Karter et al, 1999, Wei et al, 2007 and obesity (Stettler et al, 2002).…”
Section: Insert Figure 1 Discussionmentioning
confidence: 99%
“…Mother's body size and offspring birth weight were shown to be associated with ASP in both boys and girls. Birth weight was an independent contributing factor in predicting ASP and a high birth weight has been proposed as an independent risk factor for obesity (33,34). An early association between ASP and obesity can be inferred from two previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…After delivery, 15–50% of women with GDM develop type 2 diabetes later in life1. In addition, children and adolescents with higher birthweight are associated with increased risk of obesity and diabetes, based on reports from our group and others5, 6. Therefore, GDM is sometimes called ‘a disease of two generations.’…”
Section: Introductionmentioning
confidence: 99%